The SIX Family of Transcription Factors: Common Themes Integrating Developmental and Cancer Biology - Meurer, Logan; Ferdman, Leonard; Belcher, Beau; Camarata, Troy (Frontiers in Cell and Developmental Biology, 2021)
The sine oculis (SIX) family of transcription factors are key regulators of developmental processes during embryogenesis. Members of this family control gene expression to promote self-renewal of progenitor cell populations and govern mechanisms of cell differentiation. When the function of SIX genes become disrupted, distinct congenital disease develops both in animal models and humans. In addition to the embryonic setting, members of the SIX family have been found to be critical regulators of tumorigenesis, promoting cell proliferation, epithelial-to-mesenchymal transition, and metastasis. Research in both the fields of developmental biology and cancer research have provided an extensive understanding of SIX family transcription factor functions. Here we review recent progress in elucidating the role of SIX family genes in congenital disease as well as in the promotion of cancer. Common themes arise when comparing SIX transcription factor function during embryonic and cancer development. We highlight the complementary nature of these two fields and how knowledge in one area can open new aspects of experimentation in the other.